Difficulties in Open and Distance Learning Mode of Education: Students’ Perspectives - Joshi, Bishnu Maya; Acharya, Umesh; Khatiwada, Shambhu Prasad (Education and Development, 2024)
This study examines the difficulties perceived by students engaged in synchronous open and distance learning (ODL). Faculty of Education, Tribhuvan University, has embraced ODL to expand educational access, but this mode poses difficulties that require attention. A cross-sectional survey design has been applied to the investigation of the difficulties faced by ODL students. The data were collected using a Google Form survey in the form of a Likert scale. The research covers both individual-related and instructional-related difficulties. Individual-related difficulties include time management difficulties resultant from other commitments, financial constraints, lack of support from peers and family, unfavorable home learning environments, struggles with learning complex material remotely, isolation, and limited technological proficiency among the students. The instructional-related difficulties include teacher feedback delays, inadequate academic support, poor course material design, and confusion between the core text and supplementary materials. These difficulties underscore the importance of an effective instructional design, timely feedback, and instructor-student interaction. The findings suggest towards the need for targeted interventions to address individual difficulties, such as time management support, financial assistance, and improved learning environments. On the instructional side, optimizing course materials, providing timely feedback, and fostering strong instructor-student relationships are crucial. Technical and financial support and training for instructors and students to optimize course materials and increase instructor-student interaction environments are suggested for overcoming the difficulties.